Personality traits as possible mediators in the relationship between childhood trauma and depressive symptoms in Chinese adolescents. (August 2018) - Zhang, Minli; Han, Juan; Shi, Junxin; Ding, Huisi; Wang, Kaiqiao; Kang, Chun; Gong, Jiangling
Abstract: Childhood trauma has been found to be a critical risk factor for depression in adolescents. Personality traits have been linked with mental health. However, the relationship between childhood trauma, personality traits, and depressive symptoms in adolescents is largely unclear. This study tried to examine the mediating effect of personality traits between childhood trauma and depressive symptoms among adolescents. Meanwhile, the possible bidirectional association between personality traits and depression was considered in the study. A group of community-based adolescents aged 10–17 years (N = 5793) were recruited from nine schools in Wuhan city, China. The participants completed self-report questionnaires, including the Center for Epidemiologic Studies Depression Scale (CES-D), the Childhood Trauma Questionnaire (CTQ) and the NEO-Five Factor Inventory (NEO-FFI). Results showed that childhood trauma experiences were positively related with depressive symptoms and neuroticism, and negatively related with extraversion and conscientiousness; depressive symptoms were related with high neuroticism, low extraversion, and conscientiousness. Neuroticism and extraversion partially mediated the relationship between childhood trauma and depressive symptoms. And 'childhood trauma-personality traits-depression' models showed better property than the alternative models of 'childhood trauma-depression-personality traits'. The current study provides preliminary evidence for mediation roles of neuroticism and extraversion in the effect of childhood trauma to depressive symptoms in adolescents. These findings may contribute to better prevention and interventions for depressive symptoms among adolescents with childhood trauma via personality traits improvement.